The Role of Rural Women in Agriculture A case study of Algeria - BENALI, Amina (Dirassat Journal Economic Issue, 2016)
This paper provides evidence on the crucial role of women in agriculture and rural development. It presents the results of a research conducted 140 rural women in agricultural farms in western Algeria concerned women’s participation in agricultural activities. This document re affirms that women make essential contributions to agriculture and rural enterprises across the developing world. Women are major producers of food, earners of household income